A Study of the Mechanical Response of Nonwovens Excited by Plate Vibration - Jan-Lukas Archut; Ruben Kins; Yousef Heider; Frederik Cloppenburg; Bernd Markert; Thomas Gries; Burkhard Corves (Applied Mechanics, 2022)
Nonwovens are a type of textile that possess a wide range of unique properties, such as lightweight and damping characteristics, which make them suitable for many applications as in medicine and engineering. In this study, the focus lies on the mechanical response of nonwovens as a multiphase porous layer excited by an underlying vibrating plate. The material properties of the nonwovens are characterized via laboratory measurements applied to different samples. In particular, a dynamic analysis of the underlying thin plate is carried out to obtain its eigenmodes and, thus, the maximum response. These eigenmodes are then utilized in the boundary conditions in an advanced numerical porous media model to simulate the dynamic response of the anisotropic fibrous material. To understand the coupled processes in the fibrous textile material, a three-dimensional initial-boundary-value problem of porous media dynamics is introduced. The numerical results demonstrate the capability of the proposed model to realize the interplay between the pore-air pressure and the effective stresses during nonwovens vibration and, thus, the role of the pore air in vibration-induced fiber-fiber friction reduction as well as the effectiveness of the nonwovens in the dissipation of the kinetic energy, i.e., damping propagating acoustic waves.